Validating a Child Youth Resilience Measurement (CYRM-28) for Adolescents Living With HIV (ALHIV) in Urban Malawi - Kaunda-Khangamwa, Blessings N.; Maposa, Innocent; Dambe, Rosalia; Malisita, Kennedy; Mtagalume, Emmanuel; Chigaru, Lalio; Munthali, Alister; Chipeta, Effie; Phiri, Sam; Manderson, Lenore (Frontiers in Psychology, 2020)
Resilience as a strength-based notion, measured across cultures, age groups and sub-populations, contributes to understanding health and well-being. Yet, there is limited evidence of how the construct performs in resource-limited countries. We explored the psychometric properties of the CYRM-28 and validated the scale with adolescents living with HIV (ALHIV), a key sub-population. The participants included members of an advisory panel and 406 ALHIV, aged 15-19 years, attending an ART and teen-club clinic in Blantyre, Malawi. This study employed a mixed-method study using an exploratory sequential design. The advisory panel discussed the CYRM-28, and select ALHIV then translated it into Chichewa, pilot-tested it using cognitive interviews and back-translated it for clarity and appropriateness. The resultant CYRM-28 was tested using a survey with purposefully selected ALHIV. The overall median score was 123, with an interquartile range of 110-130. Minimum and maximum scores were 53 and 140. Cronbach's alpha of 0.863 and Kaiser Meyer-Olkin measure (0.866) confirmed internal consistency and the sample size adequacy, respectively. Bartlett's tests of sphericity (p-value <0.001) informed factor analysis. Exploratory factor analysis (EFA) determined possible dimensions of resilience and the sub-scales. The confirmatory factor analysis (CFA) confirmed the construct validity and supported a three-factor model consistent with the conceptualization of resilience as a multi-dimensional construct. Structural equation modelling (SEM) was applied to perform CFA to measure model of resilience. Multiple fit indices showed a good fit for the model. The CYRM-28 has good reliability and convergent validity and adequacy scores, which render it useful as a self-report resilience measure to inform and evaluate interventions for the health and well-being of adolescents in Malawi.